Specific ethnolinguistic features of gastronomic vocabulary (dairy products) in the Tuvan and Khakas languages - Kuular, Elena M.; Taskarakova, Natalya N.; Chugunekova, Alyona N. (The New Research of Tuva, 2022)
The article provides a comparative analysis of the naming units of milk and milk drinks that make up the lexical and semantic group “dairy products”. They are an invariable and important element of the material culture of two closely related Turkic peoples — the Tuvans and Khakas who have inhabited the vast territories of southern Siberia from the dawn of time. Using lexicographic sources and field data, we have found about 50 lexical units which are divided into three lexical and semantic groups: milk, milk drinks and milk dishes. The collected facts give us the opportunity to reveal the linguistic worldview of the Tuvan and Khakas ethnic groups and to determine the functioning of gastronomic vocabulary (dairy products) in modern languages. The names of dairy products in the Tuvan and Khakas languages are not the same by origin. Along with Turkic roots, there is a significant number of Mongolian elements in them, in particular in the Tuvan language. This group of words in the compared languages reflects their historical contacts with both related and unrelated peoples. In addition, in the names of dairy products we can find traces of the vocabulary that emerged as a result of the formation and development of dialects of the Tuvan and Khakas languages. It has been revealed that dialect vocabulary still exerts a noticeable impact on the contemporary literary languages of the Tuvans and Khakas. All these facts testify to the enrichment of the vocabulary of the Khakas and Tuvan languages with terms of traditional folk material culture from various sources, especially from folklore texts.